P3.196 High Prevalence of Hepatitis B (HBV) Coinfections, and Low Rate of Effective HBV-Vaccination in MSM with Known Date of HIV-1 Seroconversion in Germany. (13th July 2013) - Jansen, K; Scheufele, R; Bock, C; Gunsenheimer-Bartmeyer, B; Hamouda, O; Houareau, C; Kücherer, C; Thamm, M; Meixenberger, K
Abstract : Background: Men who have sex with men (MSM) with frequent sexual interactions are assumed to be at higher risk for HBV-infection. Due to partly similar transmission routes, HBV is a frequent coinfection in HIV-positive patients. HIV-coinfection accelerates disease progression of HBV-infection resulting in earlier and more frequent occurrence of liver cirrhosis and hepatocellular carcinoma. Thus, HBV-vaccination for HIV-positive MSM is recommended in Germany. Methods: On basis of the nationwide, multicenter, open, prospective cohort study of HIV 1-seroconverters, we screened all available, yearly collected serum samples of HIV-infected MSM for anti-HBc, anti-HBs, HBs-AG, anti-HCV and Syphilis antibodies. Samples with signs of acute/chronic HBV-infection were confirmed by PCR. Prevalences were calculated on patient basis (at least one sample tested positively). Results: 5.603 samples of 1.945 MSM were screened. Median age at HIV 1-seroconversion was 33 years. In all screened MSM, prevalences of active acute/chronic HBV were 1.9%, of cleared HBV 28.0%. 4.8% had signs of occult HBV-infection (solely anti-HBc positive). 48.6% were effectively vaccinated against HBV (titre > 10mIU/ml), of those 24.2% already at timepoint of HIV-seroconversion. Prevalences of cleared HBV and of vaccination against HBV differed significantly between age groups (table 1). 50.6% of MSM who ever had a HBV-coinfection had a further coinfection with Syphilis, 13.3% with HCV. Discussion: Despite extensive vaccination campaigns regarding HBV-infections in MSM in Germany, less than half of all screened MSM were vaccinated. Consequentially, we found a high proportion of MSM who ever had a HBV-coinfection. Of special interest was a significant subgroup of patients having signs of occult HBV-infection, a phenomenon known to occur in immune-suppressed patients. High rates of coinfections with Syphilis and HCV in HBV/HIV-coinfected MSM stress the demand for more extensive and tailored campaigns for HBV-vaccination and prevention of STI in general for MSM in Germany, especially for higher age groups.